On the problem of estimating the philosophical postmodern - Raida, Constantine (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2015)
This article explores the reasons of negative assessments of philosophical maxims such scientists as J. Bodriyar, J.F Lyotard, J. Deleuze, F. Guattari, J. Derrida, L. Iryharey, J. Lacan,M. Sera, P. Virilio and other founders of postmodern philosophy. The transformation of the role and importance of philosophical thought in public life, specific character of its historical mission and the new philosophical foundations, initiated within the postmodern paradigm are highlighted.